Low Self-Confidence Among Vocational High School Students in Sidoarjo: A Case Study - Mayya Kholidah; Isrida Yul Arifiana; Nurfi Laili (International Journal on Integrated Education, 2026)
Self-confidence is a fundamental psychological attribute that plays a crucial role in supporting students' academic achievement and social adjustment. Low self-confidence may hinder students from expressing their opinions, actively participating in classroom activities, and establishing effective interpersonal relationships. This study aimed to describe the results of a psychological assessment and evaluate the effectiveness of Group Cognitive Behavioral Therapy (CBT) in improving self-confidence among vocational high school students with low self-confidence. A case study approach was employed involving five female vocational high school students who were identified through an initial screening conducted by school guidance and counseling teachers. The assessment process included interviews, behavioral observations, Focus Group Discussions (FGDs), psychological testing using the Edwards Personal Preference Schedule (EPPS), graphic tests (Draw-A-Person [DAP], Baum Test, and House-Tree-Person [HTP]), and a self-confidence scale. The assessment findings revealed that all participants demonstrated negative self-perceptions, fear of negative evaluation, low self-esteem, limited confidence in expressing their opinions, and a tendency to avoid situations involving social evaluation. Group CBT was implemented through structured sessions focusing on identifying negative automatic thoughts, cognitive restructuring, adaptive behavioral practice, and positive behavior reinforcement. The evaluation results indicated significant improvements in self-confidence, reflected by increased willingness to speak in front of others, greater participation in group activities, enhanced ability to express personal opinions, and reduced negative beliefs about personal competence. These findings suggest that Group CBT is an effective intervention for fostering more adaptive cognitive patterns and enhancing self-confidence in both academic and social contexts. Therefore, Group CBT may serve as an effective psychological intervention within school guidance and counseling services to support students with low self-confidence.